2019
DOI: 10.1038/s41396-019-0439-3
|View full text |Cite
|
Sign up to set email alerts
|

Seeking active RubisCOs from the currently uncultured microbial majority colonizing deep-sea hydrothermal vent environments

Abstract: Almost all the inorganic carbon on Earth is converted into biomass via the Calvin-Benson-Bassham (CBB) cycle. Here, the central carboxylation reaction is catalyzed by ribulose-1,5-bisphosphate carboxylase/oxygenase (RubisCO), which can be found in numerous primary producers including plants, algae, cyanobacteria, and many autotrophic bacteria. Although RubisCO possesses a crucial role in global biomass production, it is not a perfect catalyst. Therefore, research interest persists on accessing the full potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…To identify the form of each variant, a set of manually curated variants was mapped to a phylogenetic tree and rubisco-like proteins were removed as they lack carboxylation activity, leaving % 33,000 non-redundant variants (see Materials and Methods for a detailed description of the pipeline). While rubisco enzymes that do not share sequence homology to currently identified variants are not detectable by this pipeline, so far, no evolutionarily distinct rubiscos were found (Böhnke & Perner, 2019). We, therefore, denote the set of % 33,000 sequences as the sequence space of wild rubisco's large subunit.…”
Section: Mapping the Sequence Space Of Wild Rubiscosmentioning
confidence: 99%
“…To identify the form of each variant, a set of manually curated variants was mapped to a phylogenetic tree and rubisco-like proteins were removed as they lack carboxylation activity, leaving % 33,000 non-redundant variants (see Materials and Methods for a detailed description of the pipeline). While rubisco enzymes that do not share sequence homology to currently identified variants are not detectable by this pipeline, so far, no evolutionarily distinct rubiscos were found (Böhnke & Perner, 2019). We, therefore, denote the set of % 33,000 sequences as the sequence space of wild rubisco's large subunit.…”
Section: Mapping the Sequence Space Of Wild Rubiscosmentioning
confidence: 99%
“…5E ), which is further oxidized to sulfate, producing adenosine triphosphate ( 54 , 55 ). Simultaneously, the elevated expression of RuBisCO in this microniche, which catalyzes the rate-limiting step in the CBB cycle, suggests that these periphery symbionts also fix atmospheric carbon dioxide into a biologically useful carbon source ( 17 , 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…These different habitats introduce a need for microbes to adapt quickly to an ever-changing environment which is supported by the enrichment of transposase genes and therefore an increased potential for horizontal gene transfer (46). Pagoda Chimney has the most taxonomic diversity of rbcLS genes, with a higher presence of archaeal rbcLS genes, likely due to the physical structure of the chimney allowing for many temperatures and chemical gradients (47). It has been shown that RuBisCO can also be used for nucleotide salvage rather than carbon fixation in archaea, which could explain the high abundance of archaeal rbcLS genes present (48).…”
Section: Discussionmentioning
confidence: 99%